Development and validation of an analytical method for the simultaneous determination of the alcohol biomarkers ethyl glucuronide, ethyl sulfate, N-acetyltaurine, and 16:0/18:1-phosphatidylethanol in human blood - Hofmann, Vanessa; Sundermann, Tom R.; Schmitt, Georg; Bartel, Marc (Drug testing and analysis, 2022)
As alcohol is the most common addictive substance worldwide, it is inevitable to advance the established research. New and more substantial analytical methods can be applied to reply to complex questions in legal or forensic contexts. Therefore, an analytical method for the simultaneous determination of four different alcohol biomarkers—ethyl glucuronide, ethyl sulfate, N-acetyltaurine, and 16:0/18:1-phosphatidylethanol—in human blood was developed, validated, and verified. Despite the different chemical properties of the analytes, a specific determination via HPLC-MS/MS was achieved using a novel type of a Phenomenex Luna® Omega Sugar column. Furthermore, all criteria for a successful validation were fulfilled according to forensic guidelines. The method proved to be linear and demonstrates selectivity and sufficient sensitivity for every biomarker. LODs obtained with this method of 2.6 ng/ml (EtG), 4.7 ng/ml (EtS), 12.5 ng/ml (NAcT), and 6.9 ng/ml (PEth) were in an acceptable range for routine applications, and the stability of all analytes over a range of 12 h is given. The verification of the new developed method was performed with authentic samples. Thus, whole blood and postmortem samples were analyzed to obtain information about the drinking behavior, which can answer complex questions regarding alcohol consumption.